Information Choice Technologies - Hellwig, Christian; Kohls, Sebastian; Veldkamp, Laura (American Economic Review, 2012)
Theories based on information costs or frictions have become increasing popular in macroeconomics and macro-finance. The literature has used various types of information choices, such as rational inattention, inattentiveness, information markets and costly precision. Using a unified framework, we compare these different information choice technologies and explain why some generate increasing returns and others, particularly those where agents choose how much public information to observe, generate multiple equilibria. The results can help applied theorists to choose the appropriate information choice technology for their application and to understand the consequences of that modeling choice.